2021
DOI: 10.1111/bph.15424
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D regulation of energy metabolism in cancer

Abstract: Vitamin D exerts anti‐cancer effects in recent clinical trials and preclinical models. The actions of vitamin D are primarily mediated through its hormonal form, 1,25‐dihydroxyvitamin D (1,25(OH)2D). Previous literature describing in vitro studies has predominantly focused on the anti‐tumourigenic effects of the hormone, such as proliferation and apoptosis. However, recent evidence has identified 1,25(OH)2D as a regulator of energy metabolism in cancer cells, where requirements for specific energy sources at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 140 publications
0
13
0
Order By: Relevance
“…As mentioned above, cancer metastasis is a detrimental hallmark that is rarely studied in connection to nutrients or other dietary bioactive compounds (Khadge et al, 2018; Sleeman, 2018). In this themed issue of the British Journal of Pharmacology , Sheeley et al (2022) refer to cancer as a metabolic disease and review metabolic features of tumours which allow cancer cells to proliferate and spread throughout the body (Sheeley et al, 2022). Recent knowledge on one of the most biologically active nutrients, 1,25‐dihydroxyvitamin D, demonstrates its potential as an agent targeting metabolic pathways with minimal effects on surrounding tissues and whole‐body metabolism.…”
Section: Nutrition In Targeting Metastasis the Silent Killermentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, cancer metastasis is a detrimental hallmark that is rarely studied in connection to nutrients or other dietary bioactive compounds (Khadge et al, 2018; Sleeman, 2018). In this themed issue of the British Journal of Pharmacology , Sheeley et al (2022) refer to cancer as a metabolic disease and review metabolic features of tumours which allow cancer cells to proliferate and spread throughout the body (Sheeley et al, 2022). Recent knowledge on one of the most biologically active nutrients, 1,25‐dihydroxyvitamin D, demonstrates its potential as an agent targeting metabolic pathways with minimal effects on surrounding tissues and whole‐body metabolism.…”
Section: Nutrition In Targeting Metastasis the Silent Killermentioning
confidence: 99%
“…Recent knowledge on one of the most biologically active nutrients, 1,25‐dihydroxyvitamin D, demonstrates its potential as an agent targeting metabolic pathways with minimal effects on surrounding tissues and whole‐body metabolism. Hence, Sheeley et al (2022) propose 1,25‐dihydroxyvitamin D as an alternative approach to current therapies targeting metabolism where many off‐target effects are a limitation. Glucose, glutamine and lipid metabolism appear to be regulated by 1,25‐dihydroxyvitamin D in cancer cells, which may lead to a decrease in metabolic plasticity and energy production and thus attenuate cancer progression (Sheeley et al, 2022).…”
Section: Nutrition In Targeting Metastasis the Silent Killermentioning
confidence: 99%
“…Indeed, it was rapidly established that 1,25D and a variety of synthetic VDR agonists exerted anticancer effects (including cell cycle arrest, (15) apoptosis, (16) and differentiation (17) ) in VDR-positive breast cancer cells in vitro as well as in some animal tumor models. (18)(19)(20) Other effects of 1,25D that were demonstrated in various breast cancer model systems included blockade of epithelial-mesenchymal transition (EMT), (21,22) invasion, (19) metastasis, (23)(24)(25) and energy metabolism, (25)(26)(27)(28)(29)(30) as well as induction of autophagy. (31)(32)(33)(34)(35) However, the specific mechanisms and pathways that link the 1,25D-VDR complex to the observed biological effects remain elusive and appear to be highly cell type specific based on mechanistic studies and genomic profiling as described below.…”
Section: General Anticancer Effects Of Vdr Agonists In Breast Cancer Cell Lines and Animal Modelsmentioning
confidence: 99%
“…Some of the studies reported promising antitumor activity, while others did not. Was reported that the application of high doses (20 IU/kg) of 1.25 OH) 2D3 combined with docetaxel and carboplatin was safe and well-tolerated [32].…”
Section: Combined D3 Anticancer Drugsmentioning
confidence: 99%